Survival states as indicators of learning performance and biological stress in refugee children: a cross-sectional study with a comparison group - Andrea Hahnefeld; Thorsten Sukale; Elena Weigand; Katharina Münch; Sigrid Aberl; Lea V. Eckler; Davin Schmidt; Anna Friedmann; Paul L. Plener; Jörg M. Fegert; Volker Mall (BMC Psychiatry, 2021)
Abstract Background Our goal was to accurately detect young children at risk for long-term psychiatric disturbances after potentially traumatic experiences in the course of relocation. In addition to detailed assessment of parent-rated parent and child symptomatology, we focused on disruptive behaviors in the education environment summarized as survival states, as these frequently lead to clinical referral. Methods We screened 52 refugee children aged 3–7 (M = 5.14 years, SD = 1.17) for symptoms of Posttraumatic Stress Disorder (PTSD) with the Child and Adolescent Trauma Screening (CATS) in parent rating. The parents’ mental health was assessed using the Refugee Health Screener (RHS-15). Furthermore, the child’s educators were asked to evaluate the pathological survival states of the child and we made a general assessment of the children’s symptoms with the Strengths and Difficulties Questionnaire (SDQ) rated by parents and educators. Children in the refugee sample completed a working memory learning task (Subtest Atlantis from the Kaufmann Assessment Battery for Children, KABC-II) and delivered saliva samples for testing of the cortisol level. Results The parental rating of their child’s PTSD symptoms was significantly related to their own mental well-being (r = .50, p < .001). Children with survival states in educator ratings exhibited weaker learning performance (F = 3.49, p < .05) and higher evening cortisol levels (U = 113, z = − 1.7, p < .05, one-tailed). Conclusions Survival states are promising indicators for children’s learning performance and distress level complementary to parent rating of child PTSD, which is highly intercorrelated with the parents’ own symptom load. Trial registration Trial registration number: DRKS00021150 on DRKS Date of registration: 04.08.2020 retrospectively registered